Future perfect : - Williams, William B. (Patriot's Pub., 1995)
Can we live healthier, longer lives? Can we preserve our endangered environment and conserve our limited resources? In short, is Utopia possible? In this book, Williams outlines the unique system of logic that enabled him to retire a self-made millionaire at age 39, and shows how to apply this powerful system to the myriad social, economic, and political problems we face today.